Penerapan Metode Waterfall Dalam Pengembangan Sistem Informasi Masjid - Saidi Ramadan Siregar; Pristiwanto Pristiwanto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Apart from being a congregational prayer center, the mosque can also be an information center that becomes everyone who visits it. The word congregation in prayer services has the meaning together and is led by the prayer priest. If in terms of praying, the priest holds a great responsibility for what he leads, for example, the priest should know anyone who is a follower of the imam (makmum) and should know the name, address of the congregation, even if their job. The Prophet Muhammad SAW 1500 years ago gave many examples of this in the hadith books. Rasulullah SAW led his prayers first paying attention to the congregation so that they straighten the rows (saf) and tighten them. The Prophet SAW once stroked the shoulders of the congregation while saying, straighten and tighten the rows (saf) by you because actually Satan will fill the empty rows. Apart from that, the Prophet SAW recognized each congregation, not only their names, but even every complaint that was experienced by each congregation. Therefore praying in congregation provides a solution for Muslims as long as the imam or leader can recognize and understand the current problems of the people. Along with the development of science and technology, an idea emerged on how to collect congregational data if it was collaborated with the IT world. Of course, this is by building a mosque information system that is able to record congregational visitors to the mosque. At the same time, this data can be used to track congregations if they want to be visited whose purpose is to invite congregational prayers to the mosque and provide encouragement to worshipers who are reluctant to come to the mosque